Knowledge, Attitude, and Practice of Iraqi Intensive Care Nursing Staff Regarding Pressure Ulcer Prevention - Sukaina Hafedh Ahmed; Abdul Kareem Salman Khudhair; Shima Haghani; Tahereh Najafi Ghezeljeh (Iran University of Medical Sciences, 2024)
Background: Pressure ulcers (PUs) can cause several complications in patients and lead to a poor prognosis. PU is an essential indicator of the quality of care received. The occurrence of this wound is more common and dangerous in intensive care units (ICUs). Given nurses' critical role in PU prevention, evaluating their knowledge, attitude, and practice in this area is essential. Therefore, this study assessed knowledge, attitude, and practice regarding PU prevention among ICU nurses in Al-Basra and Dhi-Qar, Iraq. Methods: This cross-sectional descriptive study investigated 231 ICU nursing staff working in hospitals in Al-Basra and Dhi-Qar from August to September 2022. The subjects were recruited through the census method. The study data were collected electronically using questionnaires to assess knowledge, attitude, and practice regarding PU prevention. Descriptive and inferential statistics, including the independent t-test, the chi-square test, and the Fisher exact test, were utilized for data analysis in SPSS software, version 22.0, at P<0.05. Results: According to the results, the Mean±SD scores of knowledge, attitude, and practice of nurses regarding the prevention of PU were 6.00±2.51, 35.52±3.97, and 24.26±5.68, respectively, indicating a lack of knowledge and unfavorable levels of attitude and practice. Moreover, a significant relationship existed between knowledge about PU and participation in in-service training programs on PU (P=0.021). There was also a positive significant relationship between the PU practice and years of practical experience in the ICU (P=0.017). Conclusion: Based on the study's findings, efficient and practical in-service nursing programs should be implemented to enhance the knowledge, attitude, and practice of ICU nurses regarding PU prevention in these hospitals.